Challenges and Countermeasures of Entrepreneurial Risk Management in Shared Bicycle Enterprises - Guo, Hengzhi (Asia Pacific Economic and Management Review, 2024)
With the rise of the sharing economy, shared bicycles, as a convenient and environmentally friendly way of travel, have been rapidly promoted and applied around the world. However, bike-sharing enterprises face many risks in the process of entrepreneurship, including market risk, technical risk, legal risk and operational risk. This paper aims to discuss the challenges of bike-sharing enterprises in entrepreneurial risk management, and put forward corresponding countermeasures, in order to provide reference for the sustainable development of bike-sharing enterprises.